Edible coatings and plant extract influence decay and biochemical attributes of nectarines - A, SOWMYASHREE; SHARMA, R R; RUDRA, SHALINI G; GROVER, MINAKSHI; SINGH, DINESH; KUMAR, RAJU (The Indian Journal of Agricultural Sciences, 2021)
Nectarine has a limited storage life of 3-4 days. During storage, it is infested by several pathogens which cause huge postharvest losses. In addition, fruits lose their quality adversely. Therefore, there is urgent need to reduce losses caused by postharvest pathogens and improve marketability of nectarine fruits by using appropriate eco-friendly approaches. Hence, we attempted the use of different coatings (carboxy methylcellulose, (CMC) and chitosan, (CH) alone and in combination with mixed plant extract (MPE) on ’Snow Queen’ nectarine fruits stored at supermarket conditions (18±2ºC 85-90% RH) for 16 days. Our results revealed that the fruit decay increased with the increase in storage period and fruits coated with layer-by-layer coatings of CMC-CH-MPE exhibited the lowest fruit decay (6.80 Â± 0.20%) which was the highest in the non-coated (control) fruits (16.10 ± 0.60 %). The respiration rate showed increasing trend up to certain storage period but then it declined in all the treatments. Similarly, total phenolics and total antioxidant activity was the highest in the CMC-CH-MPE coated fruits and the lowest in non-coated fruits whereas the PME activity was the lowest in CMC-CH-MPE coated fruits and the highest in control fruits. In all, it can be concluded that layer-by-layer coating of CMC-CH-MPE was the best treatmentfor reducing fruit decay and maintaining desirable level of biochemical attributes in Snow Queen nectarine fruits up to 16 days of storage at supermarket conditions.